2019
DOI: 10.1111/jcpt.13010
|View full text |Cite
|
Sign up to set email alerts
|

Levofloxacin‐induced rhabdomyolysis in a patient on concurrent atorvastatin: Case report and literature review

Abstract: Rhabdomyolysis is a clinical syndrome associated with electrolyte abnormalities and myoglobinuria. Signs and symptoms of rhabdomyolysis include elevated creatinine phosphokinase (CPK) and aspartate transaminase (AST), muscle pain, urine discoloration, fatigue, nausea, vomiting and fever. 1 If untreated, rhabdomyolysis can lead to renal failure and death. 2 Rhabdomyolysis can occur as a result of traumatic injury or chemical causes. 1-3 Prior case reports describing fluoroquinolone-induced rhabdomyolysis occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…A previous postmarketing analysis from the FAERS data raised a safety signal detecting 48 reports of LEV-induced rhabdomyolysis from 2004 to 2015, which had a median time to onset of a few Frontiers in Pharmacology frontiersin.org days (Carnovale et al, 2017). This interval is comparable to that of rhabdomyolysis induced by other drugs, such as antibiotics, particularly quinolone (Bouchard et al, 2019), but shorter than in paradoxical cases reported with statins (Vinci et al, 2021), with which it occurs within a few weeks to months. There was one report of a 36-year-old male who took levetiracetam for 2 years before rhabdomyolysis onset, whom we did not include in the calculation of the median onset time to avoid negative skewing of the results (Alshehabi et al, 2022).…”
Section: Discussionsupporting
confidence: 55%
“…A previous postmarketing analysis from the FAERS data raised a safety signal detecting 48 reports of LEV-induced rhabdomyolysis from 2004 to 2015, which had a median time to onset of a few Frontiers in Pharmacology frontiersin.org days (Carnovale et al, 2017). This interval is comparable to that of rhabdomyolysis induced by other drugs, such as antibiotics, particularly quinolone (Bouchard et al, 2019), but shorter than in paradoxical cases reported with statins (Vinci et al, 2021), with which it occurs within a few weeks to months. There was one report of a 36-year-old male who took levetiracetam for 2 years before rhabdomyolysis onset, whom we did not include in the calculation of the median onset time to avoid negative skewing of the results (Alshehabi et al, 2022).…”
Section: Discussionsupporting
confidence: 55%
“…Only one patient was readmitted for myopathy 3 months after the combination, but the exact timing of the ADR was not clear [12]. High-intensity statins were implicated in 5 case reports [7,[13][14]17,19], with four patients taking 80mg per day of atorvastatin and one patient using 80mg per day of simvastatin, while moderate-intensity statins in 9 case reports [9,11,13,[16][17][18][19][20][21][22]. It was unclear from two case reports about the statin dosage, one involving atorvastatin and one involving simvastatin [8] [11].…”
Section: Data Charting and Evidences Synthesismentioning
confidence: 99%
“…ADRs in the included literature were rhabdomyolysis (n = 12) [7][8][9]11,13,[16][17][18][19][20][21][22], acute hepatitis(n = 1) [15], muscle weakness(n = 1) [14], tendinopathy of hip(n = 1) [10], and myopathy(n = 1) [12] (Table 2). CK was reported in 81%(n = 13) of the case reports with a range between 183 to 816,000 units/L, which all above the normal value for CK [7][8][9][12][13][14][16][17][18][19][20][21][22].…”
Section: Data Charting and Evidences Synthesismentioning
confidence: 99%
See 2 more Smart Citations